Penerapan Realistic Mathematics Education (RME) Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Data di Kelas V SD Negeri 3 Gandatapa - Sinta Nurhana; Muryaningsih, Sri (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to improve student learning outcomes in the subject of data. The method employed was Classroom Action Research (CAR), conducted over two cycles, each consisting of two meetings and four stages; planning, action implementation, observation, and reflection. The research subjects were nine fifth-grade student at SD Negeri 3 Gandatapa, comprising four male and five female student. The findings indicate that the Realistic Mathematics Education (RME) approach effectively enhanced student learning outcomes across three domains cognitive, affective, and psychomotor. This is evident from the improvement observed in each cycle. The percentage of students achieving the cognitive learning criteria increased from 77,8% to 88,9% the average affective score improved from 2,54 to 3,29; and the psychomotor score rose from 2,49 to 3,18. thus, the success indicators for the implementation of RME were achieved, demonstrating that this approach significantly contributes to improving student learning outcomes, particularly in data-related content.